NILAI BATAS DAN INDIKATOR OBESITAS TERHADAP TERJADINYA DIABETES MELLITUS TIPE 2 - Made Dewi Susilawati; Krisnawati Bantas; Abas Basuni Jahari (Persagi, 2014)
ABSTRACTObesity is a risk factor of type 2 diabetes mellitus (T2DM), but the obesity indicator having most clear association still varies. The purpose of the study was to determine cut-off point of three different indicators of obesity body mass index (BMI), waist circumference (WC) and waist-height ratio (WHtR) and compare the three indicators of obesity in detecting of T2DM. The study was a secondary data analysis using data of baseline cohort study of non communicable desease. Total sample for the analysis was 1415 adult subjects. Multiple logistic regression and Receiving Operating Characteristic (ROC) methods implied to analyze the assosiation. The results showed that cut - off point and strength of the relationship using BMI was more than 26 kg/m2 (Se 0.65, Sp 0.64 ; Area Under the Curve (AUC) 0.67 ), OR 2.45 ( 95% CI 1.66 - 3.62 ), WC men and women was more than 81 cm ( Se 0.63 ; Sp 0.63 ; AUC 0.68 ), OR 2.43 ( 95% CI 1.65 - 3.57 ), and WHtR was more than 0.53 ( Se 0.70 ; Sp 0.60; AUC 0.69 ,) OR 2.68 ( 95% CI 1.79 - 4.01 ). The conclusion of this study is that the strength of assosiation among the three indicators of obesity and the type 2 diabetes is similar after controlled by age, family history, hypertension and physical activity.Keywords : type 2 diabetes mellitus, receiving operating characteristic, indicators of obesity, area under the curveABSTRAKBerbagai penelitian telah membuktikan obesitas sebagai salah satu faktor risiko terjadinya Diabetes Mellitus tipe 2 (DMT2), namun demikian hasilnya masih bervariasi. Tujuan penelitian adalah menentukan cut-off point tiga indikator obesitas indeks massa tubuh (IMT), lingkar perut (LP) dan rasio lingkar perut-tinggi badan (LP/TB) serta membandingkan dari ketiga indikator obesitas dalam mendeteksi terjadinya DMT2. Desain penelitian potong lintang menggunakan data sekunder 1415 sampel dewasa dari baseline studi kohort Penyakit Tidak Menular (PTM). Analisis menggunakan regresi logistik ganda dan metode Receiving Operating Characteristic (ROC). Hasil penelitian menunjukkan bahwa nilai cut-off point dan kekuatan hubungan menggunakan indikator obesitas umum IMT ≥ 26 kg/m2 (Se 0,65; Sp 0,64; AUC 0,67), OR 2,45 (95% CI 1,66-3,62), LP laki-laki dan perempuan ≥ 81 cm (Se 0,63; Sp 0,63; AUC 0,68), OR 2,43 (95% CI 1,65-3,57), dan LP/TB ≥ 0,53 (Se 0,70; Sp 0,60; AUC 0,69) OR 2,68 (95% CI 1,79-4,01). Kesimpulan dari penelitian ini bahwa kekuatan hubungan ketiga indikator obesitas terhadap terjadinya DMT2, tidak jauh berbeda setelah dikontrol umur, riwayat keluarga, hipertensi dan aktivitas fisik. [Penel Gizi Makan 2014, 37(1): 11-20]Kata kunci: diabetes mellitus tipe 2, receiving operating characteristic, indikator obesitas, area under the curve